2010
DOI: 10.1017/s0001924000004140
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the role of hyper-mixers in supersonic mixing

Abstract: Hypersonic air-breathing engines are considered to be the most appropriate alternative device to rocket based propulsion systems in reusable space vehicles within the lower atmospheric regime. Supersonic combustion ramjet (scramjet) engine is the key enabling technology for such sustained hypersonic flights. In scramjet engines, since the residence time of the mixture is of the order of a millisecond (for flight Mach numbers from 6 to 8) owing to the short combustor length, generation of useful thrust over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It was found that the 14° ramp angle gave maximum mixing, and three relieved strut gave the least degree of unmixedness due to the generation of streamwise vortices. The effect of hypermixers in improving the mixing characteristics of strut-based combustors was numerically studied by Desikan et al (2010). Five strut geometries were considered in their model combustor which was studied numerically with air as an injectant and compared to the baseline wedge-shaped strut.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the 14° ramp angle gave maximum mixing, and three relieved strut gave the least degree of unmixedness due to the generation of streamwise vortices. The effect of hypermixers in improving the mixing characteristics of strut-based combustors was numerically studied by Desikan et al (2010). Five strut geometries were considered in their model combustor which was studied numerically with air as an injectant and compared to the baseline wedge-shaped strut.…”
Section: Introductionmentioning
confidence: 99%
“…Passive methods use a specific structure inside the combustion chamber or change the configuration of the wall to form a vortex and recirculation zone in the flow, which result in improved air-fuel mixing performance for higher combustion performance. Various methods have been studied, such as pylons [3][4][5][6], cavities [7][8][9][10][11][12][13][14], hyper-mixers [15][16][17][18][19][20][21], injector locations [22], angles [23,24], and outlet shapes [25]. A pylon is a slim structure on the wall of the combustion chamber that generates a recirculation zone and vortex to promote air-fuel mixing and stabilize the flame.…”
Section: Introductionmentioning
confidence: 99%
“…A hyper-mixer is a system where a part of the wall of a combustion chamber has a form such as a ramp or a step. The shape generally induces a counter-rotating vortex, which helps to improve the mixing efficiency and expansion of the mixed area [15][16][17][18][19][20][21]. Studies have been carried out on adjusting the angle, arrangement, and shape of the injector [23-25] and using a swirler or counterflow nozzle [26,27].Unlike passive methods, active methods actively intervene in the flow of combustion chambers.…”
mentioning
confidence: 99%